2000
DOI: 10.1007/bf03020950
|View full text |Cite
|
Sign up to set email alerts
|

Acute myopathy of intensive care in a child after heart transplantation

Abstract: Purpose: Acute myopathy of intensive care has been described infrequently in children and never after organ transplantation. We report a case of acute myopathy of intensive care in a child after heart transplantation.Clinical features: An 11-yr-old girl, with no previous medical history, developed acute cardiomyopathy leading to cardiac shock. Family history revealed four cases of unidentified myopathy and/or cardiomyopathy. Preoperatively, while muscle biopsy was near normal, myocardial biopsy revealed non sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In some cases, it was very early in the onset of critical illness. [56] In the only prospective study done so far, weakness was clinically noticed after a wide range of duration of illness (4-26 days) and 86% of these children were mechanically ventilated for > 5 days. [17]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, it was very early in the onset of critical illness. [56] In the only prospective study done so far, weakness was clinically noticed after a wide range of duration of illness (4-26 days) and 86% of these children were mechanically ventilated for > 5 days. [17]…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that CIP and CIM co-exist; a condition that has been termed critical illness polyneuropathy and myopathy (CIPNM). [34] Data regarding ICUAW in children is restricted to small case series and reports[5678910111213141516] and only one prospective study has been reported so far in the pediatric age group. [17]…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] While Bolton and colleagues were studying CIP, there were also reports of single cases [10][11][12][13][14] and eventually series [15][16][17][18][19][20][21] of adult and pediatric 10 patients who developed acute myopathy during treatment of status asthmaticus. Later, a similar acute myopathy was noted to follow organ transplantation [22][23][24][25][26][27] and to occur in association with many other critical illness states in children as well as adults. [28][29][30][31][32][33][34][35] Terminology was highly variable initially, but eventually the name critical illness myopathy (CIM) was accepted.…”
Section: Historymentioning
confidence: 99%